Motor Performance in Relation with Sustained Attention in Children with Attention Deficit Hyperactivity Disorder - Solmaz Solouki; Fatemeh Behnia; Katayoun Khoushabi; Ebrahim Pishyareh; Samaneh Hossein-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: Present study compares relationship between motor performance, sustained attention and impulse control in children with Attention Deficit Hyperactivity Disorder and normal children. Materials & Methods: In this descriptive-analytic study, 21 boys with ADHD and 21 normal boys in the age range of 7- 10 years old were participated. Motor performance by using Bruininks Oseretsky Test of Motor Proficiency and sustained attention and impulse control by using Continuous Performance Test were evaluated. Results: Analysis by T-Test and Mann-Whitney revealed significant difference between ADHD group and normal group in gross, fine and battery motor performance also sustained attention and impulse control (P<0.0001). Analysis by Z-Fisher test indicated no significant difference between Correlation Coefficient of inattention and gross motor performance in two groups (P=0.276) but significant difference between Correlation Coefficient of inattention and fine (P<0.0001) and battery (P<0.0001) motor performance were shown. Correlation Coefficient impulsivity and gross (P=0.379), fine (P=0.92) and battery (P=0.562) motor performance shown no significant difference between two groups. Conclusion: According to study results there was a positive relation between sustained attention and impulse control and most of motor performance in both groups. Therefore these findings help Occupational Therapist to determine rehabilitation priorities and to use exact strategies in order to enhance motor performance in children.